The Islamic banking system as a stabilizing force in contemporary countries - Rodrigo Bochner (Journal of Islamic Economic Insights, 2025)
The Islamic banking system offers a distinctive financial alternative rooted in Islamic law (Sharia) and emphasizes ethical finance, equity, and social justice. This study argues that Islamic banking can serve as a stabilizing force in a country’s economy, particularly during financial crises. By examining the unique principles and mechanisms of Islamic banking, including risk sharing and asset-backed financing, this study aims to highlight how these features contribute to economic resilience. Through a comprehensive literature review, case studies, and empirical analysis, this study identifies the potential of Islamic banks to mitigate economic instability and promote sustainable growth. The findings indicate that Islamic banking not only provides financial services but also fosters social cohesion and economic inclusivity in the banking sector. This study concludes with recommendations for policymakers and financial institutions to create KPI indexes that show the training of new scholars for the public and investors who will create new products for Islamic banking systems to enhance economic stability.